1. VULNERABILITY OF NGHE AN HEALTH SECTOR TO CLIMATE CHANGE IN 2023 (Vietnam Journal of Community Medicine, 2025)
Objective: To determine the vulnerability of Nghe An health sector to climate change in 2023.Objectives and methods: Using the V&A Assessment Kit to assess the vulnerability and adaptive capacity to climate change in the health sector based on data collected at several research sites from January 2023 to December 2023.Results: The exposure level is at an average level, the exposure score is 2.27, the assessment score of the indicators in the “sensitive” group is 2.08, classified as medium risk.Conclusion: The vulnerability of Nghe An health sector to the impacts of climate change in 2023 is at a medium risk level.
Keywords: Climate change; vulnerability; health sector; Nghe An